2001
DOI: 10.1007/s004020100283
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation for acute ankle sprain

Abstract: The variation of practice with respect to the treatment of the acutely sprained ankle suggests a lack of evidence-based management strategies for this problem. The objective of this review was to assess the effectiveness of the various methods of immobilisation for acute ankle sprain. An electronic database search was conducted using MEDLINE, EMBASE, BIOSIS, CINAHL, Cochrane Controlled Trial Register and Current Contents. Randomised and quasi-randomised clinical trials describing skeletally mature individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 35 publications
1
68
0
6
Order By: Relevance
“…Despite the low number of studies for each outcome measure, there is some limited evidence that supervised exercises may provide benefit over conventional treatment alone. This review of the literature adds to the reviews of Kerkhoffs et al, 13,14,15 Kannus and Renstróm, 12 and Tiling et al 27 In these reviews the authors concluded that functional treatment (early exercise, the use of an external support, and eventually coordination training) was the treatment of choice for acute lateral ankle sprains. However, they did not differentiate between super vised and nonsupervised (functional) treatment, the objective of this review.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Despite the low number of studies for each outcome measure, there is some limited evidence that supervised exercises may provide benefit over conventional treatment alone. This review of the literature adds to the reviews of Kerkhoffs et al, 13,14,15 Kannus and Renstróm, 12 and Tiling et al 27 In these reviews the authors concluded that functional treatment (early exercise, the use of an external support, and eventually coordination training) was the treatment of choice for acute lateral ankle sprains. However, they did not differentiate between super vised and nonsupervised (functional) treatment, the objective of this review.…”
Section: Discussionmentioning
confidence: 87%
“…using the Delphi list 30 (Table 1), supplemented with 2 extra items derived from the Cochrane Musculoskeletal Injuries group. 15 Any disagreement was resolved by a third independent assessor (R.A.dB.). Each criterion was rated positive, negative, or inconclusive (insufficient information presented).…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…The three-dimensional scaffold provides the structural support for cell contact and matrix deposition Musumeci G et vitro culture, and can improve biophysical properties by mechanical loading. Scaffold-free constructs using alginate as an intermediate step have also been produced [53] and subjected to mechanical loading [54] . The challenge with such scaffold-free systems is producing them in a cost-effective and timely manner for clinical use, especially with autologous cells.…”
Section: Biomaterialsmentioning
confidence: 99%
“…Kerkhoffs et al 141 conducted a systematic review involving 22 studies, which concluded there was a significant benefit to weight bearing as tolerated compared to non-weight-bearing cast immobilization. Crutches or other gait assistive devices are commonly used in the early stages of tissue healing to prevent reinjury and to minimize pain as weight-bearing capacity progresses.…”
Section: Acute/protected Motion Phase Of Rehabilitation Early Weight mentioning
confidence: 99%